E-Commerceat Haziz Furniture Limited Company Website-Based Digital Marketing - Mohammad Aziz Nurritanto; Azizah Fatmawati (Lafadz Jaya Publisher, 2023)
PT. Haziz Mebel is a company engaged in specialized furniture. The problems that occur at PT. Haziz Furniture is in managing branding and buying and selling goods with the aim of increasing company revenue. All activities carried out at PT. Haziz Furniture is still done manually and in receiving goods that are not in accordance with the stock of goods in the warehouse. Therefore, the purpose of this study is to provide a solution to PT Haziz Furniture with a web-based application to promote and buy and sell more systematically. The sales and promotion system that still uses the conventional system makes PT. Haziz Mebel experienced various forms of difficulties in the company's operations. In this study using the Waterfall Method and the results of the research conducted resulted in a web-based furniture e-commerce information system at the Haziz Furniture furniture store. The expected result of this study is that by creating an information system, the manager of the Haziz Furniture company can increase revenue and can reduce miscommunication in company management.